Synthesis and Characterization of Some New Uracil Derivatives and their Biological Activity (Thamar University Journal of Natural & Applied Sciences, 2023)
This research includes the synthesis of thirty derivatives of uracil. Nucleophilic substitution reaction (thiol, alkylthio, hydrazino, thioacid,.. etc) of 4-chlorouracil afforded the corresponding derivatives. The 4-(2`-thiol-1` ,3`,4`-oxadiazole-5`-thiomethyl) uracil (12), ( N` - phenyl – 2` - thio -1` ,3`,4`-triazole-5`-methyl)-(2,6- dihydroxy-4-pyrimidinyl) sulphide (14) and 5-(2`,6`-dihydroxy-4`- pyrimidinyl thioacetamido)-1,3,4-thiadiazole-2-thiol (15), were synthesized by treatment of 4-thioacetichydrazide uracil (11) with carbon disulfide in the presence of a base or phenylisothiocyanate in the presence of base. Mannich bases of alkynyl thio derivativeis (3a & 10) were synthesized by the reaction of paraformaldehyde and secondary amine in the presence of CuCl (19a,b & 20a,b). These compounds were characterized by spectroscopic methods (IR & UV), by their elemental analysis (C,H,N) and Rf values. Biological activity of the synthesized compounds was determined